The relationship between parental attention and elementary student discipline - Siti Quratul Ain; Adelia Putri; Mitha Dwi Anggriani (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
This study aims to examine and analyse the relationship between parental attention and elementary school students' discipline. The method used is an ex post facto approach with a quantitative approach. The research population included all 78 fourth and fifth-grade students of SD Negeri 001 Buluh Cina, who were also sampled using a total sampling technique. The research instrument was a closed questionnaire whose validity and reliability had been tested. Data analysis was carried out using the Spearman Rank correlation test and the calculation of the coefficient of determination (R²). The results showed a positive and significant relationship between parental attention and student discipline, with a correlation coefficient of 0.516 and a significance value of 0.000 (<0.05). This value indicates a moderate category relationship, meaning that the higher the parental attention, the higher the level of student discipline. In addition, the coefficient of determination (R²) of 29.6% indicates that parental attention contributes to variations in student discipline, while the remaining 70.4% is influenced by other factors not examined. These findings emphasise the importance of parental involvement in the educational process, both through regular communication and more structured mentoring programs, so that it can support the formation of students' disciplined character more comprehensively.